The Effect of Anti-Smoking Campaigns on Smoking Behavior Among Youth: Case Studies in Middle Schools - Asbath, Asbath; Jiao, Deng; Irianti , Evi; Werdyaningsih , Endang; Desiana, Desiana (Yayasan Pendidikan Islam Daarut Thufulah, 2024)
Anti-smoking campaigns have been an integral part of smoking prevention efforts among youth, especially in secondary school settings. However, the effectiveness of such campaigns is still debatable due to several factors, including the influence of the social environment, cigarette promotion, and personal factors that influence smoking behavior among youth. This study aims to evaluate the effect of anti-smoking campaigns on smoking behavior among youth, focusing on a population of students in secondary schools. Through a case study approach, this research aims to provide a deeper understanding of the effectiveness of anti-smoking campaigns in changing smoking behavior among youth. The research method used in this study is a case study of several secondary schools that implemented anti-smoking campaigns. Data were collected through surveys, interviews, and direct observation of students' smoking behavior before and after the implementation of the anti-smoking campaign. The results showed that the anti-smoking campaign had a significant influence on smoking behavior among youth. There was a significant decrease in the number of students smoking after the implementation of the anti-smoking campaign, as well as increased awareness of the negative effects of smoking. The conclusion of this study confirms that anti-smoking campaigns are effective in changing smoking behavior among youth. Targeted and sustained implementation of anti-smoking campaigns can be an effective strategy in reducing smoking prevalence among secondary school students. Thus, continuous efforts are needed to improve and expand the reach of anti-smoking campaigns in school settings.